Isolation of chemically resistant bacterial strains from industrially polluted water body (Bangladesh Journal of Medical Science, 2013)
Background: Untreated disposal of chemical waste poses serious environmental hazard. An attempt was made towards presumptive identification of the major genera of microbial contaminants found in a natural pond that receives waste from a pharmaceutical industry of Gonoshasthaya Antibiotic Ltd. during the period of 2008 to 2009. Methodology: Water sample was collected and physical parameters were determined. Results: A total of 38 bacterial isolates were found from surface water, deep layer water and sediment soil but only five isolates were found to resist up to 0.1 mg/ml of phenol. Microscopic and biochemical test of five isolates presumptively identified them Staphylococcus sp, Sporosarcina sp, Bacillus sp and members of family Enterobacteriaceae. All five isolates were resistant to Amoxycillin (30?g), Erythromycin (15?g), and Penicillin-G (10units). Conclusion: Resistance against common therapeutic antibiotics indicates possible epidemiological risk. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 310-314 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15431